Diet reduces the effect of exogenous grit on tooth microwear. Issue 2 (18th June 2020) - Hua, Licheng; Chen, Jianbin; Ungar, Peter S.
Abstract : Exogenous grit adherent to the surface of food items and food fracture properties have each been considered important factors contributing to pattern and degree of tooth wear in mammals. However, the interactions between these two factors in generating distinctive microwear textures have remained understudied. Here the authors revisit in‐vitro results from simulated chewing to explore how adherent grit and physical properties of foods act together to create dental microwear textures on occlusal enamel surfaces. Results suggest that the effect of exogenous grit on microwear texture is dependent on the material properties foods to which they adhere. Grit in the absence of food causes more complex microwear surface textures than foods covered with similar levels and types of grit (for a given number of chews and angle of approach between opposing teeth). Different foods covered in grit also yield different complexity values. Grit‐laden, pliant meat, for example, results in a less complex texture than does resistant, grit‐laden raw carrot. This work implied that tooth wear assessment can benefit from considering grit load and food material properties together.